Pediatric thoracic anesthesia - (:unkn) unknown (Springer International Publishing, 2020)
Physiologic differences render children more vulnerable to the unwanted effects of the lateral decubitus position together with one lung ventilation, when compared to adults. In small children, two lung ventilation with lung retraction is a common technique for open thoracic procedures since it is safe and easily achieved. One lung ventilation can be achieved in children of all ages, when necessary, by selective mainstem intubation, bronchial blocker, or double lumen tube intubation. In small children, one lung ventilation performed with the aid of a bronchial blocker might be require the blocker to be placed outside the endotracheal tube (also called parallel), since the size limitation of the endotracheal tube might not allow for the fiber-optic scope to fit inside next to the blocker. Pain management is an important component of the management that can be effectively treated with a combination of regional anesthesia and intravenous analgesics. © Springer Nature Switzerland AG 2020.
Keywords: Pediatric bronchial blocker; Pediatric lung isolation; Pediatric lung separation; Pediatric one lung ventilation; Pediatric pain; Pediatric respiratory; Pediatric thoracoscopy; Pediatric thoracotomy; Pediatric ventilation; Pediatric/children thoracic surgery